PHYSICAL FITNESS ANALYSIS OF WEST JAVA BASKETBALL REFEREES BEFORE COMPETITION BASED ON THE ASSESSMENT OF SLEEP QUALITY, ANXIETY LEVELS AND PHYSICAL ACTIVITY - Alhadi, Dzaky
Background: One of the components that basketball referees must have is good fitness because basketball games are carried out with high activity for 40 minutes. Physical fitness is an important element in the performance of a referee. The purpose of the study was to determine the effect of sleep quality, anxiety level and activity on fitness level in basketball referees in West Java. Methods: This study is a quantitative descriptive study with 40 basketball referees in West Java as subjects. Subjects were given three questionnaires namely: sleep quality questionnaire, anxiety level questionnaire and physical activity questionnaire the subject was also given a Vo2max test with the bleep test. The measurement variables of this study were sleep quality, anxiety level and physical activity. Results: The mean and standard deviation of total subjects based on age (28.73 ± 5.01 years), height (172.68 ± 6.27 cm), weight (69.40 ± 11.86kg), and body mass index (23.20 ± 3.26 kg/m2). The results of the sleep quality regression test with the results of the tcount> table value (t-value = -1.658), with a significance <0.05 Sign.= 0.105), the results of the anxiety regression test with the results of the tcount> table value (t-value = 3.686), with a significance <0.05 (Sign. = 0.001), and the results of the physical activity regression test with the results of the tcount> table value (t-value = 5.166), with a significance <0.05 (Sign.= 0.00), these results indicate an influence between anxiety levels and physical activity and no effect on sleep quality. Conclusion: Based on the results of the research that has been done, it is obtained that the quality of sleep of basketball referees in West Java is on average poor with a percentage of 97.5% and does not have a significant effect on the level of fitness, the anxiety level of basketball referees in West Java is on average high with a percentage of 85% and has a significant effect on fitness levels and physical activity of basketball referees in West Java is on average moderate with a percentage of 82.5% and has a significant effect on fitness levels.